Last months of life of people with intellectual disabilities: A UK population‐based study of death and dying in intellectual disability community services. Issue 6 (31st May 2020) - Todd, Stuart; Bernal, Jane; Shearn, Julia; Worth, Rhian; Jones, Edwin; Lowe, Kathy; Madden, Phil; Barr, Owen; Forrester Jones, Rachel; Jarvis, Paul; Kroll, Thilo; McCarron, Mary; et al.
Abstract: Background: Population‐based data are presented on the nature of dying in intellectual disability services. Methods: A retrospective survey was conducted over 18 months with a sample of UK‐based intellectual disability service providers that supported over 12, 000. Core data were obtained for 222 deaths within this population. For 158 (71%) deaths, respondents returned a supplemented and modified version of VOICES‐SF. Results: The observed death was 12.2 deaths per 1, 000 people supported per year, but just over a third deaths had been deaths anticipated by care staff. Mortality patterns, place of usual care and availability of external support exerted considerable influence over outcomes at the end of life. Conclusion: Death is not a common event in intellectual disability services. A major disadvantage experienced by people with intellectual disabilities was that their deaths were relatively unanticipated. People with intellectual disabilities living in supported living settings, even when their dying was anticipated, experienced poorer outcomes.